The Utility of Non-Invasive Nasal Positive Pressure Ventilation for Acute Respiratory Distress Syndrome in Near Drowning Patients - June Hyeong Kim; Kyung Hoon Sun; Yong Jin Park (Journal of Trauma and Injury)
Purpose Near drowning refers to immediate survival after asphyxia due to submersion or immersion in water, which is a crucial public safety problem worldwide. Acute lung injury or acute respiratory distress syndrome (ARDS) is a common complication of near drowning. The purpose of this study was to investigate the feasibility and effectiveness of noninvasive nasal positive pressure ventilation (NINPPV). Methods This retrospective study was conducted at a tertiary emergency department. NINPPV was administered for moderate ARDS caused by submersion or immersion in patients who were older than 18 years, from January 2015 to December 2018. We collected the demographic (age, sex, length of hospital stay, and outcome), laboratory (arterial blood gas, lactate, oxygen saturation, partial pressure of oxygen divided by the fraction of inspired oxygen, complete blood count, blood urea nitrogen, and creatinine), and clinical data (acute lung injury index and ventilator failure) of the patients. A statistical analysis was performed using Statistical Package for the Social Sciences version 20.0 for Windows. Results NINPPV treatment was provided to 57 patients for near drowning, 45 of whom (78.9%) were successfully treated without complications; in 12 (21.1%), treatment was changed to invasive mechanical ventilation within 48 hours due to ARDS or acute kidney injury. NINPPV treatment was successful in 31 (75.6%) out of 41 sea-water near drowning patients. They were more difficult to treat with NINPPV compared with the fresh-water near drowning patients (p<0.05). Conclusions NINPPV would be useful and feasible as the initial treatment of moderate ARDS caused by near drowning.